Adversarial Robustness of Mistral-7B-Instruct-v0.2 and Gemma-7B on University-Level Mathematics - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 16 peer-reviewed papers addressing the following research question: How robust are Mistral-7B-Instruct-v0.2 and Gemma-7B to adversarial perturbations in problem statements within the MathOdyssey university-level mathematics subset. 8 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.5/10. This report is a machine-generated literature sy
Machine-generated literature synthesis.